Healthcare networks: trends of knowledge development in Brazil - Caroline Cechinel Peiter; José Luís Guedes dos Santos; Gabriela Marcellino de Melo Lanzoni; Ana Lúcia Schaefer Ferreira de Mello; Maria Fernanda Baeta Neves Alonso da Costa; Selma Regina de Andrade (Universidade Federal do Rio de Janeiro, 2019)
ABSTRACT Objective: To analyze the trend of scientific production about Healthcare Networks in thesis and dissertations in Brazil. Methods: documental, descriptive and exploratory study, with a quantitative approach, on the published between 2013 and 2016. The data collection was based on the catalog of theses and dissertations of Brazilian Personnel Improvement Coordination of Superior Level, during January 2018. Results: The 190 papers founded were distributed in four main classes: Integrated Healthcare Networks Management; Thematic health networks; Primary Healthcare as network Ordinator; and Professional education in healthcare networks. Conclusion: It is trend in the scientific knowledge production the study of Primary Healthcare as the ordinator of network and its interface with the other levels, the professional education in healthcare networks, the continuing education in health, focused on the healthcare networks management.